2016
DOI: 10.1182/blood-2016-01-696104
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic efficacy of BeneFIX vs Alprolix in hemophilia B mice

Abstract: Key Points Because extravascular FIX is physiologically important, FIXs circulating levels do not independently predict hemostatic potential. A saphenous vein hemophilia B mouse model shows that 7 days postinfusion FIX-Fc and FIX provide equal hemostatic protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 35 publications
3
63
0
Order By: Relevance
“…Factor IX is detected in the lymph and in the vascular wall, yet other extravascular compartments may exist. Immunohistochemical evaluation of mouse and human arteries show FIX staining on endothelial cells facing the vessel lumen and in the subendothelial region, where it co‐localizes with collagen IV, a major extracellular component of the endothelial basement membrane . Binding is reversible and mainly involves the Gla‐domain of FIX .…”
Section: Interactions Of Fixmentioning
confidence: 99%
See 2 more Smart Citations
“…Factor IX is detected in the lymph and in the vascular wall, yet other extravascular compartments may exist. Immunohistochemical evaluation of mouse and human arteries show FIX staining on endothelial cells facing the vessel lumen and in the subendothelial region, where it co‐localizes with collagen IV, a major extracellular component of the endothelial basement membrane . Binding is reversible and mainly involves the Gla‐domain of FIX .…”
Section: Interactions Of Fixmentioning
confidence: 99%
“…For example, in the Phase III trials, an EHL FIX with a larger volume of distribution showed similar haemostatic efficacy during weekly prophylaxis as an EHL FIX with a smaller volume of distribution; this was despite that a 5-fold higher FIX prophylactic dose was used in the study of the former product. [27][28][29] Factor IX is detected in the lymph 30 and in the vascular wall, [31][32][33] yet other extravascular compartments may exist.…”
Section: Extravascular Fix Binding To Collagenmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the recent observations of Cooley et al, that rFIX still provided haemostatic protection 7 days after infusion, in a murine saphenous vein bleeding model, even though no circulating FIX could be measured at that point. These authors and others have therefore suggested that plasma FIX level and terminal half-life may be a poor surrogate marker for haemostatic efficacy in HB [8,9] and distribution half-life of FIX may be clinically more predictive.…”
mentioning
confidence: 99%
“…They provide evidence that the size of an extravascular pool of FIX bound to collagen IV is the true pharmacodynamic predictor. 1 …”
mentioning
confidence: 99%